The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.still.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil structural quality under Brazilian sugarcane expansion areas using Visual Evaluation of Soil Structure (VESS)

Abstract: Cherubin, Maurício R.; Franco, André L.C.; Guimarães, Rachel M.L.; Tormena, Cássio A.; Cerri, Carlos E. P.; Karlen, Douglas; and Cerri, Carlos C., "Assessing soil structural quality under Brazilian sugarcane expansion areas using Visual Evaluation of Soil Structure (VESS)" (2017 Increasing global demand for biofuel has accelerated land-use change (LUC) in Brazil, primarily through the planting of sugarcane (Saccharum officinarum) to replace degraded pastures. The intensive mechanization associated with this LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 46 publications
10
53
0
4
Order By: Relevance
“…Significant positive correlations ( p < 0.01) of PR measurements with VESS scores at three depths show the effectiveness of VESS method in detecting compacted layers (Table 6). Similar to our results, significant relationships have been reported between VESS scores and physical soil quality attributes for different types of soils (Castioni et al., ; Cherubin et al., ; Tuchtenhagen et al., ). The PCA analysis using the varimax rotation and components extraction with Eigenvalues ≥1.0 yielded four principal components (PCs) that collectively accounted for the 80.64% variance in data (Table ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Significant positive correlations ( p < 0.01) of PR measurements with VESS scores at three depths show the effectiveness of VESS method in detecting compacted layers (Table 6). Similar to our results, significant relationships have been reported between VESS scores and physical soil quality attributes for different types of soils (Castioni et al., ; Cherubin et al., ; Tuchtenhagen et al., ). The PCA analysis using the varimax rotation and components extraction with Eigenvalues ≥1.0 yielded four principal components (PCs) that collectively accounted for the 80.64% variance in data (Table ).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, methods such as SubVESS (Ball et al., , ) or DS (Emmet‐Booth et al., ) considering below 25 cm depth are needed to assess the structural quality of conventionally tilled soils. Moreover, the beneficial effect of tillage as indicated by low VESS scores will prevail only for the short term due to the adverse impact of breaking aggregates on the loss of organic carbon (Cherubin et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize the advancement of studies about VESS in recent years, especially in Brazil, which manifest its applicability (Giarola et al 2009;2013;Müller et al 2012;Cherubin et al 2016). Although the results of the VESS have been highly correlated with other soil physical attributes evaluated in laboratory (Mueller et al 2009;Guimarães et al 2011;2013), as also observed in this study (Figure 1), this methodology provides only semi-quantitative information about the state of the soil physical quality (Mueller et al 2009).…”
Section: Structural Quality Alteration: Relations Between Visual Evalsupporting
confidence: 53%
“…de pragas e doenças, como por exemplo, a cigarrinha (Mahanarva fimbriolata) (GUIMARÃES et al, 2008) CARVALHO et al, 2016;CHERUBIN et al, 2017).…”
Section: Introductionunclassified